Postpartum long-acting contraception uptake and service delivery outcomes after a multilevel intervention in Kigali, Rwanda. Issue 3 (16th September 2020) - Espey, Julie; Ingabire, Rosine; Nyombayire, Julien; Hoagland, Alexandra; Da Costa, Vanessa; Mazzei, Amelia; Haddad, Lisa B; Parker, Rachel; Mukamuyango, Jeannine; Umutoni, Victoria; Allen, Susan; Karita, Etienne; et al.
Abstract : Introduction: Postpartum family planning (PPFP) is critical to reduce maternal–child mortality, abortion and unintended pregnancy. As in most countries, the majority of PP women in Rwanda have an unmet need for PPFP. In particular, increasing use of the highly effective PP long-acting reversible contraceptive (LARC) methods (the intrauterine device (IUD) and implant) is a national priority. We developed a multilevel intervention to increase supply and demand for PPFP services in Kigali, Rwanda. Methods: We implemented our intervention (which included PPFP promotional counselling for clients, training for providers, and Ministry of Health stakeholder involvement) in six government health facilities from August 2017 to October 2018. While increasing knowledge and uptake of the IUD was a primary objective, all contraceptive method options were discussed and made available. Here, we report a secondary analysis of PP implant uptake and present already published data on PPIUD uptake for reference. Results: Over a 15-month implementation period, 12 068 women received PPFP educational counselling and delivered at a study facility. Of these women, 1252 chose a PP implant (10.4% uptake) and 3372 chose a PPIUD (27.9% uptake). On average providers at our intervention facilities inserted 83.5 PP implants/month and 224.8 PPIUDs/month. Prior to our intervention, 30 PP implants/month and 8 PPIUDs/month were inserted at our selected facilities. Providers reported high ease of LARC insertion, and clients reported minimal insertion anxiety and pain. Conclusions: PP implant and PPIUD uptake significantly increased after implementation of our multilevel intervention. PPFP methods were well received by clients and providers.